ANALISIS KEMAMPUAN BERPIKIR KRITIS DAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Astri Dwi Hartati; Ari Hayati; Luvy Sylviana Zanthy (Journal on Education, 2019)
The purpose of the study was to understand the benefits of critical thinking skills and students' mathematical understanding skills in the subject matter of the Two Variable Linear Equation System. The study was conducted at 36 Public Junior High School Bandung in the odd semester of the 2018/2019 academic year in Bandung. The population of the activity was all students of class VIII with a sample of 30 students. The research instrument uses ability test questions. The research method used is qualitative research design. Data evaluation is done by reducing, presenting data, and drawing conclusions. This research activity can be concluded that the ability of students in SPLDV material is still low, especially in applying to daily life.